Evaluating Inclusion of Commercial Pistachio By-Product as a Functional Ingredient in Rainbow Trout Fishmeal and Plant Meal-Based Diets - Mosope F. Abanikannda; Mark B. Shiflett; Ana Rita C. Morais; Jeoungwhui Hong; Wendy M. Sealey; Jacob W. Bledsoe (MDPI AG, 2024)
To meet the growing demand for sustainable aquaculture, plant proteins are being explored as alternative sources in fish diets. However, some plant proteins can have adverse health effects on fish, prompting research into functional feed ingredients to mitigate these issues. This study investigated pistachio shell powder (PSP), rich in antioxidants, as a functional feed ingredient for rainbow trout (Oncorhynchus mykiss). The effects of PSP inclusion (0%, 0.5%, 1%, 2%) on growth performance, intestinal health, and gut microbiota were assessed in fish fed either a fishmeal (FM) or plant meal (PM) diet over a 12-week feeding period. The results indicated that PSP inclusion at 1% significantly (p < 0.05) improved weight gain and growth performance in FM treatments, with no impact on growth in PM treatments. No significant differences were observed in other growth parameters, intestinal morphology, or oxidative stress markers, although a trend toward the downregulation of inflammatory genes was noted in PM treatments at 2% PSP inclusion. PSP inclusion did not significantly alter gut microbiota alpha diversity but affected beta diversity at the 0.5% level in the FM treatments (p < 0.05). Differential abundance analysis of gut microbiota revealed taxa-specific responses to PSP, particularly the genus Candidatus arthromitus, increasing in relative abundance with PSP inclusion in both the FM- and PM-based treatments. Overall, PSP inclusion up to 2% did not have significant adverse effects on the growth, intestinal health, or antioxidant status of rainbow trout.